General Guidelines for Organic Crop Production - James J. Ferguson (EDIS)
This document is HS972, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: March 2004.